1996
DOI: 10.2105/ajph.86.12.1794
|View full text |Cite
|
Sign up to set email alerts
|

The late-stage diagnosis of colorectal cancer: demographic and socioeconomic factors.

Abstract: OBJECTIVES: This study described factors related to colorectal cancer stage at diagnosis. METHODS: Logistic regression analyses were used on data from the New York State Tumor Registry and US Census area-level social class indicators. RESULTS: After the effects of other predictors were controlled for, the odds of late-stage cancer increased as age decreased; women and African Americans were significantly more likely to have late stage than men and Whites; and individuals living in areas of low socioeconomic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
2
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(102 citation statements)
references
References 35 publications
4
92
2
3
Order By: Relevance
“…In particular, the African-American population has the highest morbidity and mortality rate owing to colorectal cancer, and the Hispanic population has the lowest screening rates, putting this group at greater risk for late-stage presentation of the disease. [6][7][8][9][10] Our research team recently investigated screening completion rates among a network of 31 federally qualified health centers (FQHCs) whose mission is to provide comprehensive primary care in areas where there are large volumes of low-income and medically underserved populations. 10,11 The screening rates among these predominantly African-American and Hispanic communities were the lowest recorded in the literature to date; only 7% of eligible patients were found to be compliant with colorectal cancer screening (predominantly FOBT).…”
mentioning
confidence: 99%
“…In particular, the African-American population has the highest morbidity and mortality rate owing to colorectal cancer, and the Hispanic population has the lowest screening rates, putting this group at greater risk for late-stage presentation of the disease. [6][7][8][9][10] Our research team recently investigated screening completion rates among a network of 31 federally qualified health centers (FQHCs) whose mission is to provide comprehensive primary care in areas where there are large volumes of low-income and medically underserved populations. 10,11 The screening rates among these predominantly African-American and Hispanic communities were the lowest recorded in the literature to date; only 7% of eligible patients were found to be compliant with colorectal cancer screening (predominantly FOBT).…”
mentioning
confidence: 99%
“…[19][20][21][22] African Americans have exhibited higher rates of late-stage CRC diagnosis and less overall decline in colorectal deaths than whites over the past decade. [23][24][25] Barriers to CRC screening include the inconvenient or impractical nature of the tests, [26][27][28][29] the embarrassing or unpleasant nature of the tests, 28,29 fatalistic cancer beliefs, 30,31 and participants not wanting to know that something is wrong. 28,32,33 Studies of African Americans have shown that these barriers and others, such as lack of physician recommendation, limited CRC knowledge, and the uncomfortable nature of tests, may contribute to inadequate screening 16,[34][35][36] Although prior qualitative studies have explored how knowledge, socio-culturally mediated attitudes and perceptions, and testing preferences influence screening for breast and prostate cancer among African Americans, [37][38][39][40] few qualitative studies have been conducted with African Americans on CRC screening.…”
mentioning
confidence: 99%
“…[17,18] Although numerous studies across various cancers have shown that poor SES has been associated with late-stage diagnosis, this has not been consistently observed in studies looking at NSCLC in isolation. [18][19][20][21] Disparities in access to healthcare and its use, as well as lack of preventive healthcare services including cancer screening, may contribute somewhat to differentials in cancer stage distributions, especially in late-stage diagnosis. [18,[22][23][24][25] …”
Section: In Practicementioning
confidence: 99%